Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) Pada Siswa Sekolah Dasar - Cahya Mulat, Trimaya; Yuriatson, Yuriatson; Asmi, A. Syamsinar; Rukina, Rukina (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Health improvement is an effort in national development to achieve awareness, willingness and ability to live a healthy life for every population in realizing the degree of public health. The implementation of health development is directed at increasing awareness, willingness, and ability to live to have PHBS in the family, school, and community environment. This community service activity aims to provide education about PHBS to elementary school students in State Elementary Schools. The method of implementing activities is in the form of education consisting of counseling, video screening, discussion, and question and answer. The participants of the educational activity were students of SDN Kaccia. The material presented was washing hands with soap before and after eating, brushing teeth, and doing community service work with residents of the school environment to create a healthy environment. This community service activity succeeded in increasing participants' knowledge and understanding of PHBS and increasing knowledge. PHBS educational activities in schools can be continued in other areas as an effort to foster clean and healthy living behaviors at an early age